1988
DOI: 10.1038/hdy.1988.91
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism and genetic control of high molecular weight glutenin subunits in wild tetraploid wheat Triticum turgidum var. dicoccoides

Abstract: Polymorphism of the high molecular weight glutenin subunits was studied in 456 accessions of the wild wheat Triticum turgidum var. dicoccoides (2n = 4x = 28; genomes AABB), originating from 21 populations in Israel. A total of 50 different SDS PAGE migration patterns were observed, resulting from the combinations of 15 subunit patterns of the A genome and 24 subunit patterns of the B genome. Most migration patterns consisted of five subunits, varying between three and six. The migration patterns of the A genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 26 publications
2
26
0
1
Order By: Relevance
“…This fraction represents 10% -40% of the total endosperm storage proteins, and is composed of different subunits, varying in molecular weight from 11,000 to 136,000 Dalton. Here the high molecular weight (HMW) glutenins (molecular weight above 70,000 Dalton) were studied (Levy et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…This fraction represents 10% -40% of the total endosperm storage proteins, and is composed of different subunits, varying in molecular weight from 11,000 to 136,000 Dalton. Here the high molecular weight (HMW) glutenins (molecular weight above 70,000 Dalton) were studied (Levy et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In the first of these studies, Vallega and Waines (1987) reported three new Glu-A1 alleles and six new Glu-B1 alleles. Subsequent studies by Levy et al (1988), Ciaffi et al (1993), andPflüger et al (2001) reported several additional new subunit patterns. These alleles represent potential sources for improvement of quality characteristics.…”
Section: Introductionmentioning
confidence: 93%
“…Gene silencing also occurs in wild wheat, but wild tetraploid species with four subunits are not uncommon. Analysis of the genes controlling HMW glutenin subunits can be further complicated by faint bands described as 1Ax 0 and 1By 0 by Levy et al (1988). Because these bands appeared to be coded by the same genes as the 1Ax and 1By subunits, they could be produced by proteolytic digestion, post-translation modification, premature transcriptional termination, incomplete reduction during glutenin separation, or re-oxidation during electrophoresis.…”
Section: Introductionmentioning
confidence: 96%
“…In particular, y-type subunits encoded by the Glu-A1 locus are expressed in T. monococcum, T. boeoticum, T. urartu, T. turgidum subsp. dicoccoides and T. araraticum (Waines and Payne 1987, Levy et al 1988, Margiotta et al 1996, Randhawa et al 1997. In contrast, the Glu-A1y locus is silenced in bread wheat and durum wheat (Harberd et al 1987(Harberd et al , D'ovidio et al 1996.…”
Section: Triticummentioning
confidence: 99%
“…Most of these can be crossed readily with cultivated wheat without the use of specialized methods. Electrophoresis analyses of progenitor wild wheats have demonstrated a high level of allelic variation at the loci encoding gluten proteins; several of these genes have been cloned and sequenced , Li et al 2006, Borghi et al 1996, Ciaffi et al 1998, Blatter et al 2004, Vallega and Waines 1987, Levy et al 1988, Ciaffi et al 1993, Borghi et al 1996, Jiang et al 2009). The most interesting feature of this material is that in some lines both x-and y-type subunits encoded by the Glu-A1 locus are expressed (Fig.…”
Section: Triticummentioning
confidence: 99%